Highly selective detection of 2, 4, 6-trinitrophenol by using newly developed terbium-doped blue carbon dots. Issue 9 (2nd March 2016) - Chen, Bin Bin; Liu, Ze Xi; Zou, Hong Yan; Huang, Cheng Zhi
Abstract : Tb-CDs were firstly prepared through one-step direct carbonization method for highly selective detection of TNP. Abstract : The detection of nitroaromatic explosives is of great importance owing to their strong explosive power and harmfulness in terms of the environment, homeland security and public safety. Herein, rare earth-doped carbon dots with multifunctional features were firstly prepared by simply keeping the mixture of terbium(iii ) nitrate pentahydrate and citric acid at 190 °C for 30 min. The as-prepared terbium doped carbon dots (Tb-CDs), through a rapid and simple direct carbonization route, have a size of about 3 nm, and exhibit excitation wavelength dependent emission of blue fluorescence, are stable, and can be applied for the selective and colorimetric detection of 2, 4, 6-trinitrophenol (TNP) in the range of 500 nM–100 μM with a limit of detection of 200 nM based on the inner filtering effect (IFE) of the excitation and emission bands of Tb-CDs by TNP and the electron transfer (ET) from Tb-CDs to TNP, giving a precise and highly reproducible result for detecting complex water samples.